ON THE STATE AND PROSPECTS OF RUSSIAN LANGUAGE PROFICIENCY - Sariev A. B. (American Journals, 2023)
The article deals with the data on the level of knowledge of Russian language in a technical university revealed on the basis of control teaching. The methods, techniques, forms and types of work in the training of the Russian language and the special types of tasks and exercises for deeper assimilation of grammar and speech norms of the Russian language by students are determined.
Keywords: Method, technique, norm, vocabulary, grammar, combination, teaching.